Assessing the Iraqi general budget in light of corruption and fluctuations in oil prices, and their repercussions on unemployment rates after 2003 - كزار, مصطفى حميد (Journal of Economics and Administrative Sciences, 2020)
The researcher highlighted the general budget in Iraq for the period (2003-2018) facing the challenges of administrative and financial corruption, in addition to the fluctuations in oil prices, the repercussions and many problems suffered and will suffer the Iraqi government in the process of preparing the general budget of the state and weak contribution of the agricultural and industrial sectors and other economic sectors and neglect altogether, oil has become the main supplier in funding Iraq's budget after 2003, and the impact on the unemployment rates in Iraq, which recorded fluctuating rates and then increased during the period (2012-2018) to achieve this, an inductive method was adopted, using theoretical and descriptive analysis.The decline in oil prices globally has a negative impact on the economy of Iraq after falling to the lowest levels to record the price of a barrel low levels, causing a crisis in the sources of funding for the country, forcing Iraq to resort to the policy of austerity between 2014-2018, Has not been officially approved in the country and continued austerity crisis for the year (2019), and its impact on the simple Iraqi citizen and take a series of austerity measures, including the suspension of appointments in the state departments and scholarships and foreign development courses for state employees due to lack of revenues and budget deficit pay the government. The resort to borrowing from the International Monetary Fund and the World Bank and other countries and economic conditions unfair made the economy of Iraq to the domination of foreign countries and the offer of foreign debt in the long term led to the growing economic problems, including the problem of unemployment through the pressure of expenses with the aggravation of manifestations of economic corruption in all forms in all circles the state and not to benefit from the revenues achieved for the financial budgets of previous years. The researcher proposes to prepare a stable financial budget that guarantees the sovereignty of Iraq through the need to combat corruption and activate non-oil sources in financing the public budget, develop and support other economic sectors, reform the tax system and the role of foreign investment in Iraq on economic terms to achieve public benefit.